A case study on the application of Mahalanobis-Taguchi system for magnetic component - Mohd Yazid, Abu; Sri Nur Areena, Mohd Zaini; N.N.N.M., Kamil (Penerbit Universiti Malaysia Pahang, 2021)
Control chart is a graphical record for visualizing the variations that occur in the central tendency and dispersion of a set of observations to achieve the process stability. The company under study mentioned that when the assignable causes have been eliminated from the process to the extent that the points plotted on the control chart remain within the control limits, the process is in a state of control or stable. Therefore, the company simply assumes that 10 parameters at magnetic component workstation are significant. However, by solely relying on the control chart to confirm the significant parameter is not sufficient. The purpose of the research is to emphasize on the SNR gain towards the magnetic component in production environment specifically visual mechanical inspection (VMI) at E&E industry. MTS works by classifying both normal and abnormal observations and optimize various parameters in workstation to produce better quality product. This work considered annual data of 2018. This work found that positive gain through signal to ratio (SNR) indicated the quality of system still in good condition from January with 0.3298 until December with 0.3667 after insignificant variable have been removed. This work also suggested height of excess plastic header as one of variables in VMI should be removed since the variable does not contribute to the system as shown in 2018. Meanwhile, there are two parameters reduced in March (Number of epoxy spot on winding coil and height of excess plastic header), July and August (Condition of marking and height of excess plastic header) and November (Number of scratches and height of excess plastic header). This concluded that MTS is a practical method for classification and optimization in the industry.